PERCEIVED ORGANIZATIONAL SUPPORT DAN TALENT MANAGEMENT TERHADAP KINERJA KARYAWAN MELALUI EMPLOYEE ENGAGEMENT - AYU WAHYUNI, RIA (Jurnal Ilmu Manajemen (JIM), 2019)
Abstract This research aims to determine and explain the effect Of Perceived Organizational Support and Talent Management on Employee Performance through Employee Engagement In PT PLN (Persero) UP2B East Java. This is a causal research with quantitative approach. The sample collecting technique is using sample saturation with 56 respondent of permanent employee PT PLN (Persero) UP2B East Java. The statistical analysis technique used is Structural Equation Model (SEM) with smartPLS.3 program. The results showed that Perceived Organizational Support had a and negative and insignificant effect on Employee Engagement,Talent Management had a significant and positive effect on Employee Engagement, Perceived Organizational Support has a negative and insignificant effect on Employee Performance through Employee Engagements as an intervening variable, Talent Management has a positive and significant effect on Employee Performance through Employee Engagement as an intervening variable. Keywords: employee performance; employee engagement; talent management perceived organizational support